MENINGKATKAN KEMAMPUAN KOMUNIKASI MATEMATIS DAN SELF EFFICACY SISWA SMP MENGGUNAKAN PENDEKATAN REALISTIC MATHEMATICS EDUCATION - Wulandari, Rehan; Kusumawati, Julfah Rodiyah; Kadarisma, Gida (IKIP Siliwangi, 2018)
This study aims to analyze how the ability of mathematical communication and Self Efficacy by using Realistic Mathematics Education (RME) approach in junior high school students. The research method used is quasi-experimental using two classes, first class as experiment class and second class as control class. The experimental class uses the Realistic Mathematics Education (RME) approach while the control class uses conventional learning. In both classes, pretest and initial questionnaire were conducted to determine the initial ability of each class, and at the end of the two classes postest. The results of this study were processed and analyzed using Mann-Whitney test. The results showed that communication skills and self-efficacy of students whose learning using Realistic Mathematics education are better than those using conventional learning.